Korelasi Pelayanan Kefarmasian dan Citra Rumah Sakit dalam Analisa SWOT Instalasi Farmasi RS Baptis Batu - Charina Halim Sugiono; Rollando Rollando; FX. Haryanto Susanto; Eva Monica (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Good pharmacy services are expected to build the positive image of the hospital. This includes the enhancement of competitive advantage among hospitals. The expected output of this research is identifying the effect of three dimensions of pharmacy services; interpersonal relations, therapy management and general satisfaction, to the image of the Baptis hospital, Batu City. The implementation of SWOT analysis is expected to determine the effect between variables, and the hospital can improve the competitive advantage. This study used quantitative and qualitative methods. Quantitative research involved 200 respondents and the method of statistical analysis was Multiple Linear Regression to investigate the effect of pharmacy services on the hospital image. The results of the study prove that pharmacy personnel at the Pharmacy Installation of Baptist Hospital Batu has provided good service, cared for patients, showed respect, and gave their willingness to provide information, education, counseling, and good activities. While the rating is classified as low, but still in good range is the patient's response time which is in the dimensions of general patient satisfaction. Qualitative research used the SWOT analysis and involved pharmacists of the Baptis Hospital. Generally, the result of statistical analysis revealed that the dimensions of pharmacy services have a positive effect on the hospital hospital image, both partially and simultaneously. In addition, the result of SWOT analysis demonstrated that Baptis Hospital is included in the first quadrant, which means the hospital runs a strategy that leads to the growth of the hospital. The hospital is in the perfect position that allows the management to rely on the strength in order to develop rapidly.